Causes of Cheating in Exams and Its Treatment - Shaker , Osama (Islamic Sciences Journal, 2023)
ABSTRACT This is a discussion of a dangerous disease that spreads among our students, until they thought it permissible, and some even thought it was a delegate , this disease is cheating in exams, so I explained in this research, after its definition, that its ruling is prohibition, then I touched on the reasons why students cheat in order to avoid them. After that, I spoke about the effects of cheating, whether its effects on the students themselves or the community. Then, after all, I summarized the most important educational preventive treatments that should be taken into account in order to stop the spread of this disease among our students, and in order to graduate a conscious generation that can advance our society forward.